Synthetic cathinone MDPV downregulates glutamate transporter subtype I (GLT-1) and produces rewarding and locomotor-activating effects that are reduced by a GLT-1 activator. (September 2016) - Gregg, Ryan A.; Hicks, Callum; Nayak, Sunil U.; Tallarida, Christopher S.; Nucero, Paul; Smith, Garry R.; Reitz, Allen B.; Rawls, Scott M.
Abstract: Synthetic cathinones produce dysregulation of monoamine systems, but their effects on the glutamate system and the influence of glutamate on behavioral effects related to cathinone abuse are unknown. A principal regulator of glutamate homeostasis is glutamate transporter subtype 1 (GLT-1), an astrocytic protein that clears glutamate from the extracellular space and influences behavioral effects of established psychostimulants. We hypothesized that repeated administration of the synthetic cathinone, MDPV (3, 4-methylenedioxypyrovalerone), would affect GLT-1 expression in the corticolimbic circuit, and that a GLT-1 activator (ceftriaxone, CTX) would reduce rewarding and locomotor-stimulant effects of MDPV in rats. GLT-1 protein expression in the nucleus accumbens (NAcc), but not prefrontal cortex (PFC), was decreased following withdrawal (2, 5 and 10 days) from repeated MDPV treatment, but not immediately after the last MDPV injection. CTX (200 mg/kg) pretreatment did not affect acute locomotor activation produced by MDPV (0.5, 1, 3 mg/kg). However, CTX (200 mg/kg) administered during a 7-day MDPV treatment paradigm attenuated the development of MDPV-induced sensitization of repetitive movements in rats challenged with MDPV following 11 days of drug abstinence. Pretreatment with CTX (200 mg/kg) during a 4-day MDPV (2 mg/kg) conditioned place preference (CPP) paradigm reduced the development of place preference produced by MDPV. The present data demonstrate dysregulation of corticolimbic glutamate transport systems during withdrawal from chronic MDPV exposure, and show that a GLT-1 transporter activator disrupts behavioral effects of MDPV that are related to synthetic cathinone abuse. Highlights: No studies have evaluated a role for glutamate in synthetic cathinone pharmacology. MDPV withdrawal reduces GLT-1 expression in the nucleus accumbens. GLT-1 activator ceftriaxone attenuates MDPV-induced behavioral sensitization. GLT-1 activator ceftriaxone attenuates MDPV-induced CPP.